Concurrent validity of the international physical activity questionnaire in outpatients with bipolar disorder: Comparison with the Sensewear Armband. (30th March 2016) - Vancampfort, Davy; Wyckaert, Sabine; Sienaert, Pascal; De Herdt, Amber; De Hert, Marc; Rosenbaum, Simon; Probst, Michel
Abstract: The International Physical Activity Questionnaire (IPAQ) is a self-report questionnaire commonly used in mental health care settings to assess physical activity. However, despite its frequent use, its validity has not been investigated in people with bipolar disorder. The aim of this pilot study was to examine the concurrent validity of the energy expenditure recorded with the IPAQ compared with an objective measure, the Sensewear Armband (SWA). Twenty outpatients with bipolar disorder wore a SWA for 8 full consecutive days and subsequently completed the IPAQ. There was a significant correlation between the active (moderate and vigorous physical activity) energy expenditure as assessed with the IPAQ and SWA (minimum 10 min bouts). The IPAQ overestimated active energy expenditure and underestimated total energy expenditure from physical activity by almost 40% compared with the SWA. Results demonstrate that the IPAQ should be used with caution as a measure for estimating energy expenditure from physical activity in outpatients with bipolar disorder. Highlights: The IPAQ overestimates active energy expenditure. The IPAQ should be used with caution in mental health populations. There is need for a valid physical activity tool for people with bipolar disorder.